2017
DOI: 10.1038/s41598-017-12922-2
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene, a natural phenolic compound, synergizes the antineoplastic effects of megestrol acetate in endometrial cancer

Abstract: Endometrial cancer is the most common gynecologic cancer in the United States and its incidence and mortality has been rising over the past decade. Few treatment options are available for patients with advanced and recurring endometrial cancers. Novel therapies, which are frequently toxic, are difficult to establish in this patient population which tends to be older and plagued by comorbidities such as diabetes mellitus and hypertension. Therefore, novel, non-toxic therapies are urgently needed. Megestrol acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Similarly, in a athymic nude mouse model of diffuse large B-cell lymphoma, pterostibene (30 mg/kg) markedly inhibited tumor growth, reduced MMP, increased cellular apoptotic index and ROS levels, leading to S-phase arrest in the cell cycle (Kong et al, 2016). More importantly, it was demonstrated that pterostilbene (30 mg/kg) with megestrol acetate (10 mg/kg) significantly reduced HEC-1A tumor growth in an endometrial cancer xenograft mouse model as compared to pterostilbene or megestrol acetate alone (Wen et al, 2017). At in vitro level, the above combination suppressed ERK and STAT3 signaling pathways and estrogen receptor expression.…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 96%
“…Similarly, in a athymic nude mouse model of diffuse large B-cell lymphoma, pterostibene (30 mg/kg) markedly inhibited tumor growth, reduced MMP, increased cellular apoptotic index and ROS levels, leading to S-phase arrest in the cell cycle (Kong et al, 2016). More importantly, it was demonstrated that pterostilbene (30 mg/kg) with megestrol acetate (10 mg/kg) significantly reduced HEC-1A tumor growth in an endometrial cancer xenograft mouse model as compared to pterostilbene or megestrol acetate alone (Wen et al, 2017). At in vitro level, the above combination suppressed ERK and STAT3 signaling pathways and estrogen receptor expression.…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 96%
“…Herein, we were investigating polyphenols from stilbenoid class, such as RSV and its natural dimethylated analog PTS, and their epigenetic effects in breast cancer cells. Stilbenoids were shown to exert anti‐cancer effects in cell lines and in vivo models, however, without a clear molecular mechanism demonstrated . There are a few reports by us and others on the involvement of epigenetics and specifically DNA methylation in the action of stilbenoids .…”
Section: Discussionmentioning
confidence: 99%
“…Certain dietary constituents have been shown to exert beneficial effects in cancer, including polyphenols from grapes and blueberries, namely resveratrol (RSV) and its dimethylated analog pterostilbene (PTS) . These compounds were shown to have anti‐cancer properties; however, studies to date have been exploratory and limited without direct mechanistic input .…”
Section: Introductionmentioning
confidence: 99%
“…Western blots were performed as described previously [ 27 ]. Cells were grown in complete medium overnight and treated with DMSO or pterostilbene at various concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, pterostilbene (PTE), a natural, dimethylated resveratrol analog with higher bioavailability, has recently become of increasing interest [ 15 , 16 , 17 , 18 ]. Its strong antitumor activity, low toxicity, and commercial availability as well as its low cost, has rendered PTE as an attractive agent for adjuvant therapy in malignancies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. As healthcare costs rise, interest in natural supplements with strong anti-tumor properties has increased, and pterostilbene represents an appealing novel therapeutic agent in chronic cancers such as ovarian cancer, where recurrent disease is common, and long-term goals include maintenance of quality of life along with longevity.…”
Section: Introductionmentioning
confidence: 99%